Nanotechnology-Driven Strategy Against SARS-CoV-2: Pluronic F127-Based Nanomicelles with or Without Atazanavir Reduce Viral Replication in Calu-3 Cells - Eduardo Ricci-Junior; Alice Santos Rosa; Tatielle do Nascimento; Ralph Santos-Oliveira; Marcos Alexandre Nunes da Silva; Debora Ferreira Barreto-Vieira; Luísa Tozatto Batista; Giovanna Barbosa da Conceição; Tayane Alvites Nunes Quintão; Vivian Neuza Santos Ferreira; Milene Dias Miranda (Viruses)
Despite extensive efforts, no highly effective antiviral molecule exists for treating moderate and severe COVID-19. Nanotechnology has emerged as a promising approach for developing novel drug delivery systems to enhance antiviral efficacy. Among these, polymeric nanomicelles improve the solubility, bioavailability, and cellular uptake of therapeutic agents. In this study, Pluronic F127-based nanomicelles were developed and evaluated for their antiviral activity against SARS-CoV-2. The nanomicelles, formulated using the direct dissolution method, exhibited an average size of 37.4 ± 8.01 nm and a polydispersity index (PDI) of 0.427 ± 0.01. Their antiviral efficacy was assessed in SARS-CoV-2-infected Vero E6 and Calu-3 cell models, where treatment with a 1:2 dilution inhibited viral replication by more than 90%. Cytotoxicity assays confirmed the nanomicelles were non-toxic to both cell lines after 72 h. In SARS-CoV-2-infected Calu-3 cells (human type II pneumocyte model), treatment with Pluronic F127-based nanomicelles containing atazanavir (ATV) significantly reduced viral replication, even under high MOI (2) and after 48 h, while also preventing IL-6 upregulation. To investigate their mechanism, viral pretreatment with nanomicelles showed no inhibitory effect. However, pre-exposure of Calu-3 cells led to significant viral replication reduction (>85% and >75% for 1:2 and 1:4 dilutions, respectively), as confirmed by transmission electron microscopy. These findings highlight Pluronic F127-based nanomicelles as a promising nanotechnology-driven strategy against SARS-CoV-2, reinforcing their potential for future antiviral therapies.